To find the product \( W \times G \) where \( W = 3x - 2 \) and \( G = 4x - 1 \), we can use the distributive property (also known as the FOIL method for binomials).
Let's calculate:
\[ W \times G = (3x - 2)(4x - 1) \]
Now, we apply the distributive property:
- First: \( 3x \times 4x = 12x^2 \)
- Outer: \( 3x \times (-1) = -3x \)
- Inner: \( -2 \times 4x = -8x \)
- Last: \( -2 \times (-1) = 2 \)
Now, combine all these results:
\[ W \times G = 12x^2 - 3x - 8x + 2 \]
Combine the like terms (the \( x \) terms):
\[ 12x^2 - 11x + 2 \]
So the final product is:
\[ 12x^2 - 11x + 2 \]
From the options given, the correct response is:
12x² - 11x + 2